Team Scaffolds: How Mesolevel Structures Enable Role-Based Coordination in Temporary Groups - Valentine, Melissa A.; Edmondson, Amy C. (Organization Science, 2015)
This paper shows how mesolevel structures support effective coordination in temporary groups. Prior research on coordination in temporary groups describes how roles encode individual responsibilities so that coordination between relative strangers is possible. We extend this research by introducing key tenets from team effectiveness research to theorize when role-based coordination might be more or less effective. We develop these ideas in a multimethod study of a hospital emergency department (ED) redesign. Before the redesign, people coordinated in ad hoc groupings, which provided flexibility because any nurse could work with any doctor, but these groupings were limited in effectiveness because people were not accountable to each other for progress, did not have shared understanding of their work, and faced interpersonal risks when reaching out to other roles. The redesign introduced new mesolevel structures that bounded a set of roles (rather than a set of specific individuals, as in a team) and gave them collective responsibility for a whole task. We conceptualized the mesolevel structures as team scaffolds and found that they embodied the logic of both role and team structures. The team scaffolds enabled small-group interactions to take the form of an actual team process with team-level prioritizing, updating, and helping, based on newfound accountability, overlapping representations of work, and belonging—despite the lack of stable team composition. Quantitative data revealed changes to the coordination patterns in the ED (captured through a two-mode network) after the team scaffolds were implemented and showed a 40% improvement in patient throughput time.